Lead intoxication in a puppy - a case report - E. Srebočan; J. Pompe-Gotal; I. Kiš; B. Pirkič; B. Artukovič; Z. Špacir-Prskalo (Veterinární Medicína, 2002)
Lead intoxication in a puppy is described. The puppy was submitted to surgical procedure for suspicion of acute abdominal pain. Diagnosis was established on the basis of the presence of eroded lead weights in stomach, biochemical and hematological blood tests as well as by elevated tissue lead concentrations.